2020
DOI: 10.3390/app10072290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant and Antimicrobial Activities of Porcine Liver Protein Hydrolysates Obtained Using Alcalase, Bromelain, and Papain

Abstract: In order to make the by-products generated from the porcine industry more valuable, pig livers were used in this trial to obtain protein hydrolysates. Three proteases (alcalase, bromelain, and papain) were utilized for enzymatic hydrolysis with two different durations, 4 and 8 hours. Ultrafiltration process was used for the recovery of the extracts, employing three different membrane pore sizes (30, 10, and 5 kDa). The porcine livers contained considerable amounts of protein (19.0%), considering they are almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…However, other sources such as poultry by-products (bones, feet, and skin) have emerged owing to regulation, religions restrictions, or culture traditions [ 72 ]. Several types of enzymes have been tested for their extraction such as Alcalase, bromelain, flavourzyme, papain, or pepsin, with papain, pepsin, and Alcalase being those that reported the most successful results for releasing antioxidant biopeptides from animal tissues [ 73 , 74 ]. In this regard, López-Pedrouso et al [ 43 ] found that the use of Alcalase in the enzymatic hydrolysis of porcine liver displayed better results than those obtained with bromelain, flavourzyme, and papain.…”
Section: Physiological Properties Of Food-derived Bioactive Peptidesmentioning
confidence: 99%
“…However, other sources such as poultry by-products (bones, feet, and skin) have emerged owing to regulation, religions restrictions, or culture traditions [ 72 ]. Several types of enzymes have been tested for their extraction such as Alcalase, bromelain, flavourzyme, papain, or pepsin, with papain, pepsin, and Alcalase being those that reported the most successful results for releasing antioxidant biopeptides from animal tissues [ 73 , 74 ]. In this regard, López-Pedrouso et al [ 43 ] found that the use of Alcalase in the enzymatic hydrolysis of porcine liver displayed better results than those obtained with bromelain, flavourzyme, and papain.…”
Section: Physiological Properties Of Food-derived Bioactive Peptidesmentioning
confidence: 99%
“…In this case, the HORAC test was used to ensure the obtaining of functional proteins with good antioxidant capacity, which would make it possible to avoid the excessive amounts of antioxidant additives necessary during storage. For their part Borrajo et al [ 109 ] employed the ORAC, FRAP, DPPH • , and ABTS •+ techniques to determine the antioxidant capacity of porcine liver protein hydrolysates obtained through different conditions (enzymes, times, and filtering). With these four tests, they reported that the ideal conditions for obtaining peptides with antioxidant capacity were the use of Alcalase enzyme with subsequent ultrafiltration through a 30 kDa membrane.…”
Section: Applications Of Antioxidant Assays In Meat and Meat Productsmentioning
confidence: 99%
“…Once the peptide sequences have been identified they can be cross-checked with databases containing known BAP sequences and/or identify known BAP sequences present in larger peptides or in proteins. Examples of types of BAP activities researched in this fashion are ACE inhibition ( Lafarga et al., 2017 ), antioxidant activity ( Bechaux et al., 2020 ; Borrajo et al., 2020 ; López-Pedrouso et al., 2020 ; Yu et al., 2017 ), immunomodulating activity, and antimicrobial activity ( Borrajo et al., 2020 ; Capriotti et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%